An energy-efficient collaborative strategy of maintenance planning and production scheduling for serial-parallel systems under time-of-use tariffs. (15th April 2023) - An, Xiangxin; Si, Guojin; Xia, Tangbin; Wang, Dong; Pan, Ershun; Xi, Lifeng
Highlights: An energy-efficient collaborative strategy for serial-parallel systems is developed. Relationships between maintenance, production, and impacts of TOU tariffs are explored. An energy-efficient two-stage maintenance (ETM) strategy is proposed. A machine-level dynamic multi-attribute maintenance planning is carried out. System-level electricity cost savings are realized by idle time insertion between production. Abstract: The industrial sector is the largest consumer of total energy in the world, with the majority of its consumption in the form of electricity. Recently, to strengthen the capacity building of peak load regulation, many countries have implemented time-of-use (TOU) tariffs to encourage manufacturing enterprises to shift their electricity consumption from on-peak hours to mid-peak and off-peak hours. It brings the urgent requirement for energy-efficient operation and maintenance (O&M) schedules in manufacturing enterprises, among which the maintenance planning and production scheduling (MPPS) are both highly correlated to electricity consumption under this time-varying electricity charging modes. To tackle this key issue, a complex MPPS problem for serial-parallel manufacturing systems under TOU tariffs is studied in this paper. To solve the problem, an energy-efficient two-stage maintenance (ETM) strategy is developed to minimize the sum of the total electricity cost and tardiness cost. In the first stage, the preventive maintenance (PM) planning is presented to obtain the multi-attribute PM intervals for each machine, considering machine availability, maintenance cost, and the potential impact of planned PM actions on average electricity price. Based on the PM intervals, a mixed-integer programming model is proposed for a hybrid flow shop schedule with PM actions in the second stage. Finally, the results confirm the effectiveness of this ETM strategy in achieving electricity cost savings and ensuring system productivity, which can provide instructions for the operation of industrial enterprises.